Assessment of health care cost for complex surgical patients: review of cost, re‐imbursement and revenue involved in pancreatic surgery at a high‐volume academic medical centre. Issue 4 (9th October 2014) - Kachare, Swapnil D.; Liner, Kendall R.; Vohra, Nasreen A.; Zervos, Emmanuel E.; Hickey, Todd; Fitzgerald, Timothy L.
Abstract Background Pancreatic surgery is complex with the potential for costly hospitalization. Methods A retrospective review of patients undergoing a pancreatic resection was performed. Results The median age of the study population was 64 years. Half of the cohort was female (51%), and the majority were white (62%). Most patients underwent a pancreaticoduodenectomy (PD) (69%). The pre‐operative age‐adjusted Charlson comorbidity index was zero for 36% (n = 50), 1 for 31% (n = 43) and ≥2 for 33% (n = 45). The Clavien–Dindo grading system for post‐operative complication was grade I in 17% (n = 24), whereas 45% (n = 62) were higher grades. The medians direct fixed, direct variable, fixed indirect and total costs were $2476, $15 397, $13 207 and $31 631, respectively. There was a positive contribution margin of $7108, whereas the net margin was a loss of $6790. On univariate analyses, age, type of operation and complication grade were associated with total cost (P ≤ 0.05), whereas operation type and complication grade were associated with a net margin (P = 0.01). These findings remained significant on multivariate analysis (P < 0.05). Conclusions Increased cost, reimbursement and revenue were associated with type of operation and post‐operative complications.